A Literature Review of Technology NFT: Potential Investment, Safety Transaction and Regulations in Indonesia Case: English - Ninin Nadya; Yuniarti Hidayah Suyoso Putra (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2023)
The Non-Fungible Token was first published in 2014, but studies exploring accounting and regulatory considerations regarding Non-Fungible Token are still limited, especially in Indonesia. This study aims to uncover opportunities, challenges, regulations, and accounting considerations in Non-Fungible Token. The research method used is qualitative research with a literature review approach. The data was collected from four databases to search for papers published from 2018 to 2022 with the help of Publish or Perish, and Mendeley software. The data analysis technique was carried out by following the analytical procedure of Miles & Huberman (1994), and using Vos Viewer software to map and visualize the themes. The results of the mapping based on the determined keywords described the relationship between Non-Fungible Token and various aspects. Non-Fungible Token has potential prospects in the future, but also has an impact that cannot be ignored. Strong regulation enable to reduce the negative skepticism and impact towards Non-Fungible Token